Clash between Traditional Values and Modern Beliefs in A Silence of Desire by Kamala Markandaya: Exploring the Confrontation of Traditional and Modern Ideologies (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Kamala Markandaya the pseudonym of Kamala Purnaiya Taylor, one of the most talented women writers of Indian fiction in English, was born to a well-connected Brahman family. Her novel A Silence of Desire (1960), explores the theme of the clash between traditional values and modern beliefs, between faith and reason. Dandekar is a middle class clerk who is happily married to Sarojini.